Changes in the Pedagogical Content Knowledge (PCK) Self-Efficacy of Pre-Service Physics Teachers: Redefining the Role of Influencing Factors - Zeni Haryanto; Shelly Efwinda; Nurul Fitriyah Sulaeman (Postgraduate, University of Mataram, 2023)
Self-efficacy intervention in curriculum design is an effort to improve the quality of teaching practice for pre-service teachers. This research aims to redefine how pre-service teachers' self-efficacy changes through Physics Learning and Microteaching courses. Interventions are given by designing lectures with mastery of knowledge, guidance, teaching experience, and reflection on teaching experience. The intervention carried out 32 meetings (with a total of 67 hours) in 1 semester. The data collection techniques used a questionnaire consisting of 18 statements and reasons for giving the score through pre-test, mid-test, and post-test. The participants were 51 students in teacher education institutions in Indonesia. The results show that integrating activities such as delivering information about PCK, guidance, and their experience in teaching increased their self-efficacy. Still, their self-efficacy decreased after the teaching experience and reflection on their experience. These results recommend that teaching practice reflection activities should not be the last resort in improving students' self-efficacy. Providing information, guidance, teaching practice, and reflection should become an iterative process, where self-reflection notes as a tool to enhance their performance deficiencies and self-efficacy can be improved